Pengaruh Konten Tiktok Dr. Yessica Tania terhadap Keputusan Pembelian Produk Skincare Wanita - Angela Seprilian Nevanda Sihura; Effiati Juliana Hasibuan; Taufik Wal Hidayat (Universitas Medan Area, 2022)
The title of this research is The Influence of dr. Yessica Tania’s TikTok Content on the Decision to Purchase Women's Skincare Products. This research was conducted to prove the effect of dr. Yessica Tania’s TikTok content on the decision to buy women's skincare products. The theory used is AIDDA theory (Attention, Interest, Desire, Decision, Action) and Source Credibility Theory. Quantitative methods, data collection using questionnaires, as well as other sources such as books, journals, and others used in this study. To determine the sample, the Slovin formula was used so that the number of samples obtained was 100. In accordance with the purpose, the hypothesis in this study was tested by correlation test product moment using the SPSS version 22.0 application and the determinant test. From the results of the research that has been carried out, it is obtained: (a) the results of the correlation test product moment show that Ho is rejected and Ha is accepted, which means that there is a relationship between dr. Yessica Tania’s TikTok content on the decision to purchase women's skincare products, (b) the results of the determinant test show that the influence of dr. Yessica Tania’s TikTok content on the decision to purchase women's skincare products is 59.7%.